Patient comprehension of hip arthroscopy: an investigation of health literacy. Issue 2 (15th June 2020) - Waryasz, Gregory R; Gil, Joseph A; Kosinski, Lindsay R; Chiou, Daniel; Schiller, Jonathan R
Abstract: Several studies have demonstrated that patients have significant impairments in understanding their injury and appropriate course of management in orthopedic surgery. The purpose of this investigation is to determine if patients are able to obtain a fundamental understanding of the requisite care associated with hip arthroscopy. Any patient who elected to have hip arthroscopy was prospectively recruited to participate in the study. All patients were told they would be asked to complete a questionnaire about their surgery and post-operative instructions. The answers to each question of the questionnaire they would receive at the first post-operative visit were verbally given to each patient during the pre-operative visit. They were also given a post-operative instruction sheet on the day of surgery that contained answers to the questionnaire. At the first post-operative visit, all patients were then asked to complete a multiple-choice questionnaire prior to seeing the surgeon. A total of 56 patients (14 males, 42 females) were enrolled. All patients reported they had read the post-operative instruction sheet. The average number of correct answers was 6.5 ± 0.6 (95% CI 6 − 7) out of 11 questions (59% correct response rate ±18% [95% CI 52 − 66%]). Although we made significant pre-operative oral and written efforts to help patients achieve an elementary level of health literacy regarding their forthcoming hip arthroscopy, many patients did not achieve satisfactory comprehension. Even with instruction and information given verbally and physically (via post-operative instruction sheet) patients did not obtain satisfactory comprehension of their surgical procedure. New ways (through video, simplified cartoons or verbal explanations) must be considered in educating patients concerning surgical procedures to increase comprehension and health literacy.